Decree-Law Of The President Of The Republic No. 104 Of The Year 2012 On Amending Some Provisions Of The Stamp Duty Law Issued As Per Law No. 111 Of The Year 1980 = قرار رئيس جمهورية مصر العربية بالقانون رقم 104 لسنة 2012 بتعديل بعض أحكام قانون ضريبة الدمغة الصادر بالقانون رقم 111 لسنة 1980 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.